A model of intrapulse effects for pulse sources above 100 MHz and their measurement by an Expert System. (11th May 2009) - Fitch, Phillip
This paper describes a digital model of intrapulse effects generated from a library of source characteristics, together with the noise. The model provides simulation for amplitude, frequency and Phase Modulation (PM) effects within a pulse. Multiple modulations can occur within the same pulse. An Expert System is described which identifies and demodulates the intrapulse modulation and the results from an implementation of such a system are compared with the source data. The intrapulse model is intended for use in the evaluation of algorithms utilising traditional Digital Signal Processing (DSP) and artificial intelligent techniques associated with Electronic Support (ES) and Radar Warning Receiver (RWR) systems.